STUDI POPULASI DAN POLA PENGGUNAAN RUANG MONYET EKOR PANJANG (Macaca fascicularis) DI HUTAN PENDIDIKAN GUNUNG WALAT - Yanto Santosa; Andoko Hidayat; Abdul Haris Mustari (Media Konservasi, 2013)
Long-tailed macaque (Macaca fascicularis Raffles 1821) in Gunung Walat University Forest (HPGW) was introduced in 1980/1981. Thirty years post-introduction, there was no any research on the species. The objectives of the research were to estimate demographic parameters and home range of long-tailed macaque in HPGW. This research was conducted from March to May 2012. These data were collected using concentration count method based on sex and age structure. Composition and structure of vegetations analyzed using line-plot sampling method. The groups movement of the long-tailed macaque were recorded using GPS and analyzed using maximum convex polygon. Four groups of long-tailed macaque were observed in HPGW. Population size were 108 individual and group sizes were 30, 23, 24, 31 respectively. Population density were 0,3 per Ha, natality was 0,24, mortality juvenile to sub adult was 0,64 and mortality sub adult to adult was 0,30. Population of macaque groups indicated progressive population based on age structure. Homerange of the groups were 29,26 Ha;  19,73 Ha; 26,94 Ha and 15,78 Ha for group A, B, C, D respectively. Dominant factors of habitat of the long-tailed macaque were elevation (X1), temperature (X2) and moisture (X3). Based on the dominant factor of the habitat, the result from multiple linear regression was Y=-30,964+0,028X1+0,675X2+0,317X3, where Y=size group, R2=75,3%. Key words: long-tailed macaque, demographic parameters, population, home range, Gunung Walat Education Forest